2017
DOI: 10.1177/0194599817709436
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Lateral Cartilage Graft Tympanoplasty

Abstract: Objective To describe a novel technique for lateral graft tympanoplasty. Study Design Case series with chart review. Setting Tertiary care university hospital. Subjects and Methods Pediatric and adult patients with tympanic membrane perforations deemed unfavorable for a medial graft technique due to the perforation characteristics or myringitis. Results Between 2014 and 2016, 34 ears from 31 patients underwent a transcanal endoscopic lateral cartilage graft tympanoplasty. The mean age was 24.4 years (range, 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…near-total perforations and also perforations with extensive myringitis 18 . This study revealed a GIR of 88% with a tragal cartilage-perichondrium graft and statistically significant ABG improvement of 13.8 dB.…”
Section: Wick Et Al (2017) Validated Transcanal Endoscopic Lateral Tympanoplasty In Total Ormentioning
confidence: 99%
“…near-total perforations and also perforations with extensive myringitis 18 . This study revealed a GIR of 88% with a tragal cartilage-perichondrium graft and statistically significant ABG improvement of 13.8 dB.…”
Section: Wick Et Al (2017) Validated Transcanal Endoscopic Lateral Tympanoplasty In Total Ormentioning
confidence: 99%
“…The surgery is typically performed by making incisions in the posterior ear canal skin adjacent to the tympanic membrane. The canal skin and tympanic membrane are elevated together, which allows the surgeon to visualize the entire middle ear space [10]. Fixation or erosion of the malleus, incus or stapes can be repaired using a tympanoplasty approach using either autologous material or prosthetic materials (PORP-partial ossicular replacement prosthesis, TORP-total ossicular replacement prosthesis).…”
Section: Common Surgical Proceduresmentioning
confidence: 99%
“…The previously elevated canal skin is repositioned on the anterior canal wall with slight overlap onto the cartilage-perichondrium graft, and the vascular strip is returned to its original position over the pedicled perichondrium. 1…”
mentioning
confidence: 99%